2010
DOI: 10.1111/j.1751-2980.2010.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin resistance and point mutations in the 23S rRNA gene in Helicobacter pylori isolates from Malaysia

Abstract: In our experience, PCR-RFLP is a rapid and precise method to detect the resistance of H. pylori to clarithromycin. Using this method, a low prevalence of clarithromycin resistance was detected in our local Malaysian strains. This augurs well for the continued use of clarithromycin as a first line drug in the treatment and eradication of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
1
29
1
1
Order By: Relevance
“…These results were consistent with data obtained from other authors from studies conducted in Iran in 2011 (the rate of clarithromycin resistance was 31.7%, all of them had A2143G mutation detected using PCR-RFLP) [16] and more recently in USA in 2016 (clarithromycinresistant H. pylori was common and observed in 32.3 % of cases; the specific variants A2142G and A2143G were detected using DNA sequencing) [17]. However, the rates of A2142G and A2143G mutation in our study were significantly higher than those reported from a study conducted in Malaysia in 2010 (only one sample with A2142G mutation and two samples with A2143G mutation were found among 105 samples, accounted for only 2.9%) [18], but significantly lower than the one in Yamade's study conducted in Japan (the mutation rate was 55.6% including 82 samples with A2143G mutation and 3 samples with A2142G) [19].…”
Section: Discussioncontrasting
confidence: 75%
“…These results were consistent with data obtained from other authors from studies conducted in Iran in 2011 (the rate of clarithromycin resistance was 31.7%, all of them had A2143G mutation detected using PCR-RFLP) [16] and more recently in USA in 2016 (clarithromycinresistant H. pylori was common and observed in 32.3 % of cases; the specific variants A2142G and A2143G were detected using DNA sequencing) [17]. However, the rates of A2142G and A2143G mutation in our study were significantly higher than those reported from a study conducted in Malaysia in 2010 (only one sample with A2142G mutation and two samples with A2143G mutation were found among 105 samples, accounted for only 2.9%) [18], but significantly lower than the one in Yamade's study conducted in Japan (the mutation rate was 55.6% including 82 samples with A2143G mutation and 3 samples with A2142G) [19].…”
Section: Discussioncontrasting
confidence: 75%
“…Also, various results have been reported in other countries. In a study in Malaysia, the prevalence of the point mutation A2143G among 105 H. pylori strains was 1.9% (2/105), which is close to its prevalence in our work (6). In a study from Turkey, of 37 H. pylori-positive specimens, four (10.8%) had the A2143G mutation and 11 (29.7%) had the A2144G mutation.…”
Section: Discussionmentioning
confidence: 80%
“…It is understood from the foregoing articles that the prevalence of the point mutations vary widely from region to region. The reasons for these different results are difficult to explain, but may be due to differences in the prescription and administration of clarithromycin (6,21). In fact, the primary risk factor for resistance to clarithromycin is the previous use of clarithromycin or other macrolides (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations